ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 873 K/PID/2020 TENTANG PEMERIKSAAN PERKARA NEBIS IN IDEM: Analysis Of Decision Of The Supreme Court Number 873 K/Pid/2020 Concerning The Examination Of The Nebis In Idem - Firdaus, Zainudin; Gultom, Elfrida Ratnawati (AMICUS CURIAE, 2024)
The purpose behind this composing is to talk about the assessment of the ne bis in idem case which was reconsidered by the South Jakarta Area Court. Will a case that has been inkracht be resubmitted in an assessment strategy at the Locale Court (Ne bis inidem) and what is the legitimate thought of the board of judges in the High Court choice Number 873 K/Pid/2020 concerning Assessment of the Nebis In Idem Case? This is the primary issue in this postulation. The composition of this postulationdepends on standardizing research, which is enlightening scientific by utilizing optional information which is investigated subjectively with the logical strategy as an end. In view of the examination led, it tends to be presumed that (1). Cases that have been inkracht at the High Court level must be reconsidered at the High Court, as specified in Part XVIII of the Criminal Strategy Code concerning Phenomenal Legitimate Cures by Cassation In light of a legitimate concern for Regulation as well as Legal Survey. Sothat in the event that a reconsideration is completed at the Region Court level, it should utilize another case number that isn't important for the connected subordinate case number. ( 2). The lawful outcomes of the High Court Choice Number 873 K.Pid/2020on the subsidiary of choice number 1036/Pid. B/2018/PN Jkt. Sel put forth the defense Ne bis in Idem in light of the fact that it brought about 2 (two) ultimate conclusions out of 1 (one) case number satisfying the components of Article 76 of the Crook Code.